Potensi Pembangkit Listrik Tenaga Surya Atap Gedung Sekolah di Kota Denpasar - Kristiawan, H.; Kumara, I.N.S.; Giriantari, I.A.D. (Jurnal SPEKTRUM; Vol 6 No 4 (2019): Jurnal SPEKTRUM, 2019)
Solar Power Generation System (PLTS) is a power generation system that utilizes sunlight as a renewable energy source and a rooftop as a place for solar panels. This paper presents the results of a study of the potential of a rooftop-based solar power plant in the city of Denpasar by taking a location on the roof of the SD Negeri 5 Pedungan Diponegoro No. 60 Denpasar road using PLTS objects that have been installed. The study was carried out with the help of Heliospoce software. Based on the study, information was obtained that the potential of solar energy was 1912.8 kWh / m2 / year or an average of 5.2 kWh / m2 / day in the city of Denpasar. Sunlight that can produce electricity starts at 07.00 -18.30 WITA. The installed energy potential of PLTS is 3214.6 kWh with an angle corresponding to the roof angle of 30.96o. The result of the potential energy produced will be greater if the installation of PV uses the optimal angle (15o) that is equal to 3407kWh.